Compensatory orthodontic treatment of Angle Class II malocclusion with posterior open bite - Torres,José Newton (2013)
The present case report addresses the treatment of an Angle Class II malocclusion in an adult female patient, long face pattern, with posterior open bite and dental arches extremely expanded, due to previous treatment. The patient and parents rejection to a treatment with orthognathic surgery led to orthodontic camouflage of the skeletal discrepancies. This clinical case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO) as one of the requirements to become a BBO Diplomate.